Analyzing Sportsman Intentions to Stay in a Team from Branding and Talent Management Perspective in China: Mediating Role of Player Recruitment Strategy, Sports Team Climate and Career Success - Zhongliang SONG; Yulong GUI; Jing AN (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The most important goal of successful human resource management of a sports organization is to ensure the intention of the players to stay in the organization and to attract talented players from outside. The basic purpose of the current study is to explore the impact of sports employer branding orientation and talent management on players’ intention to stay along with the mediating impact of effective recruitment strategy, sports team climate and subjective career success. In other words, this study has been designed to understand the ways through which the retention and attraction levels of talented players can be increased. For this purpose, data has been collected from 394 players that are playing for different football clubs in China. The results indicate that player branding orientation has a positive but an insignificant impact on players’ intention to stay. However, the impact of the other independent variable i.e. talent management has a significant and positive impact on player intention to stay. As far as the mediating variables are considered, it has been found out in the results that all the mediating variables i.e. effective recruitment strategy, sports team climate and subjective career success have significant mediating impact in both cases i.e. in the relationship between sports employer branding orientation and player intention to stay; and in the relationship between talent management and player intention to stay. Various theoretical, practical and policy-making implications of this study have been thoroughly discussed by the researcher in the concluding sections.